Malawi : Staff Report for 2009 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that Malawi's macroeconomic performance has improved significantly over the past two years, and the country's agricultural-based economy has weathered the global economic storm relatively well. Good weather and the distribution of subsidized fertilizer have contributed to robust growth and moderate inflation in recent years. Malawi's medium-term outlook is favorable, within the context of successful implementation of the Extended Credit Facility-supported program. Growth is expected to remain buoyant, but moderate somewhat relative to the high growth of the recent past.